2011
DOI: 10.1111/j.1600-0897.2010.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis‐Associated Infertility: Double Intrauterine Insemination Improves Fecundity in Patients Positive for Antiendometrial Antibodies

Abstract: Double IUI improves fecundity in AEA+ patients. E-associated infertility is better diagnosed by the AEA assay than by surgery. Double IUI should be attempted prior to assisted reproductive technologies in AEA+ patients with normal fallopian tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Subit in a study of 1243 patients found double IUI to be significantly better in patient with endometriosis and antiendometrial antibodies. 12 The study recommends double iui before resorting to more invasive and expensive treatment options. Timing of performing double IUI has been debated.…”
Section: Discussionmentioning
confidence: 99%
“…Subit in a study of 1243 patients found double IUI to be significantly better in patient with endometriosis and antiendometrial antibodies. 12 The study recommends double iui before resorting to more invasive and expensive treatment options. Timing of performing double IUI has been debated.…”
Section: Discussionmentioning
confidence: 99%
“…Subit and co‐workers reported the presence of AEA in the sera of women with endometriosis affected fecundity and thus affected the success of an IUI cycle. They further reported lower clinical pregnancy rates in women with endometriosis and there was five times increased clinical pregnancy in women with double IUI cycle 93 . AEAs have also been reported to be associated with higher miscarriage rates 94 .…”
Section: Role Of Anti‐endometrial Antibodies (Aeas) In Female Inferti...mentioning
confidence: 92%
“…Nine studies were identified affecting the reproductive system and possibly altering the possibilities for a successful IVF cycle [82,83,84,85,86,87,88,89,90]. Four of the aforementioned studies concerned ASA [87,89,90,91], 3 AEA [83,86,88], one AGA [82] and one aLN1 in the follicular fluid of women with endometriosis [85]. Although ALN1 is not classified as a reproductive-specific antibody, the study population is diagnosed with endometriosis, a conditioned that has been associated to aLN1 [92].…”
Section: Auto-antibodies Specifically Affecting the Reproductive Smentioning
confidence: 99%
“…According to the results of that study, IVF outcome may be negatively correlated with certain subtypes of AEA. Examining another perspective, the presence of AEA in the sera of female patients may impede their fecundity and the success of an IUI cycle [83]. In all three groups (with endometriosis, without endometriosis, and without laparoscopic investigation) of the study, women diagnosed as AEA positive were associated with a lower CP rate.…”
Section: Auto-antibodies Specifically Affecting the Reproductive Smentioning
confidence: 99%